Biowaiver Monograph for Immediate‐Release Solid Oral Dosage Forms: Fluconazole. Issue 12 (13th October 2014) - Charoo, Naseem; Cristofoletti, Rodrigo; Graham, Alexandra; Lartey, Paul; Abrahamsson, Bertil; Groot, D. W.; Kopp, Sabine; Langguth, Peter; Polli, James; Shah, Vinod P.; Dressman, Jennifer
<x xml:space="preserve">Abstract</x> Literature data pertaining to the decision to allow a waiver of in vivo bioequivalence (BE) testing requirements for the approval of immediate release (IR) solid oral dosage forms containing fluconazole as the only active pharmaceutical ingredient (API) are reviewed. The decision is based on solubility, dissolution, permeability, therapeutic index, pharmacokinetic parameters, pharmacodynamic properties, and other relevant data. BE/bioavailability (BA) problems and drug–excipients interaction data were also reviewed and taken into consideration. According to the biopharmaceutics classification system (BCS), fluconazole in polymorphic forms II and III is a BCS class I drug and has a wide therapeutic index. BE of test formulations from many different manufacturers containing different excipients confirmed that the risk of bioinequivalence because of formulation and manufacturing factors is low. It was inferred that risk can be further reduced if in vitro studies are performed according to biowaiver guidelines. Thus, it is concluded that a biowaiver can be recommended for fluconazole IR dosage forms if (a) fluconazole is present as polymorphic form II or III or any other form/mixture showing high solubility, (b) the selection of excipients be limited to those found in IR drug products approved in International Conference on Harmonisation (ICH) countries for the same dosage form and used in their usual amounts, and (c) both the test and comparator dosage form are very rapidly dissolving, or, rapidly dissolving throughout the shelf life with similar dissolution profiles at pH 1.2, 4.5, and 6.8. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3843–3858, 2014